“Exploring the Impact of Self-Efficacy and Social Support on Type II Diabetes Self- Management in Dehradun, Uttarakhand - Vandana,; Anuj Nautiyal, (The Bioscan, 2025)
Introduction : “Diabetes mellitus (DM) is one of the most prevalent and pressing public health challenges worldwide. In particular, inadequate self-care among individuals with type 2 diabetes can result in poor glycemic control, increased risk of complications, and even mortality”. The objective of the study to observe Self-efficacy and social support in Type II diabetes self-management : A correlational, cross-sectional design with a convenient sample of 450 participants was chosen from the population of Dehradun was used to conduct this study. Two questionnaires were administered: (A) the demographic and medical data questionnaire; (B) diabetes self-care activities questionnaire. The majority of participants were employed (49.8%). The gender distribution was relatively balanced, with 48.7% identifying as male and 51.3% as female. In terms of age, 48.4% of the participants were aged 50 years or older. Analysis of HbA1c levels revealed that 42.4% of the participants had readings in the 7–8.9% range, indicating that a substantial proportion exhibited suboptimal glycemic control. Impact of Self-Care activities on self-efficacy indicates an increase in self-efficacy post-intervention. The 95% confidence interval (CI) for the difference ranges from -0.461 to -0.416, signifying a consistent improvement in self-efficacy scores across participants. Social support and self-efficacy were related to medication adherence in diabetic patients, and social support can improve medication adherence in patients with diabetes by affecting self-efficacy. In summary, clinicians can focus on interventions that enhance patients’ confidence in managing their health and adhering to prescribed medications. Educational programs, counselling, and regular follow-up discussions can be beneficial in building and sustaining self-efficacy, and adjustments to treatment plans and support strategies can be made based on changes in the patient’s socioeconomic factors, self-efficacy, and educational background over time.